DULKADIRAN, MEDIA MASYARAKAT SAMPURNAN UNTUK MEMPEROLEH KESELAMATAN, PAHALA, SYAFAAT, DAN SURGA - Nilna Fadlillah (UIN Raden Mas Said Surakarta, 2017)
This paper tries to describe the practice of reading Qur’an in the Dulkadiran tradition practiced by Sampurnan society ethnographically, in order to find its meaning. Based on the interpretation of cultures theory found out that the Sampurnan society recognizes the concepts that are based on the religious basis, which has ultimate meaning as a way to get the salvation, reward, and paradise. These concepts were then believed as the true and real, which then formulated into various symbols in the Dulkadiran tradition. These symbols have meaning that refers to those concepts and suggested certain lifestyle or action, which is delivered persuasively by Kiyai. Through these concepts, people were then motivated to perform Dulkadiran tradition. The practice of this tradition was able to create moods of a person, which then reflected into the daily life, and felt as if to justify the existing concepts, so the motivations and moods seem uniquely realistic.